Preventive interventions for the marble statues preserved in the Museum of the Roman Theater - Guelma – - bouzid, fouad (The Algerian Historical Journal, 2026)
The Roman Théâtre Museum of Guelma preserves archaeological artifacts that reflect the level of civilized man, similar to the marble statues kept there, which are exposed to a number of various influencing factors between internal and external by influence direct or indirect, by weakening the material that is made of it, which is marble, and perhaps the most important of these are natural factors. Which have greatly contributed to the damage and deterioration of marble statues, as the change in color and the texture becomes rough, in addition to human factors through negligence and indifference, which result in scratches, fractures and writings, and from this point of view we have made a diagnostic study marble statues, and illuminated them by offering a number of preventive solutions using techniques and methods to preserve it.